PESANTREN SAINS: EPISTEMOLOGY OF ISLAMIC SCIENCE IN TEACHING SYSTEM - Yusuf, Mohamad Yasin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Muslims around the world mostly was under the domination of the West in the mastery of science and technology. Establishing educational institutions that are based on science and technology is one of the ways to solve the problem.This study had the purpose to examine the epistemology of science in the teaching system in SMA Trensains boarding school Tebuireng Jombang. Applying the method of field research through qualitative approach and philosophical analyses, this study revealed that SMA Trensains Tebuireng Jombang applied "Islamic Science" in which science is constructed based on the revelation of God. It is meant that in Islamic epistemology, revelation and the Sunnah are the sources which are inspiring for building sciences. It is hoped that the building the Islamic epistemology of science will bear pious Muslim generation in religious field and proficient in science and technology, and it will impact to the glory of Islamic civilization in the future.***Pada umumnya, umat Islam di dunia ini berada di bawah dominasi Barat dalam penguasaan ilmu dan teknologi. Pendirian lembaga pendidikan yang didasarkan pada ilmu dan teknologi merupakan salah satu cara untuk mengatasi masalah tersebut. Kajian ini bertujuan untuk meneliti epistemologi ilmu dalam sistem pengajaran di SMA Trensains di pondok Pesantren Tebuireng Jombang. Dengan menggunakan metode penelitian lapangan dan dengan pendekatan penelitian kualitatif serta analisis filosofis, kajian ini menemukan bahwa SMA Trensains Tebuireng Jombang menerapkan Sains Islam, di mana ilmu dibangun berdasar wahyu Tuhan. Maksudnya adalah bahwa dalam epistemologi Islam wahyu dan sunnah adalah sumber yang memberikan inspirasi bagi pembangunan ilmu pengetahuan. Diharapkan pembangunan epistemologi Islam untuk ilmu pengetahuan akan melahirkan generasi Muslim yang shalih dalam bidang agama dan ahli dalam bidang ilmu pengetahuan dan teknologi, yang pada gilirannya akan memberikan dampak bagi kejayaan peradaban Islam di masa yang akan datang.